Work, family and women’s well-being in Malaysia - Noor, Noraini M.; Mohd Mahudin, Nor Diana (Springer Netherlands, 2016)
In this chapter we examine work, family and women’s well-being in Malaysia. We begin by briefly positioning education as a prerequisite to women’s labor force participation and highlighting this development over the last few decades. We then discuss studies in the work-family literature from two fronts: one focusing on work and family life in relation to women’s well-being, and another examining work-life balance policies and practice. On the basis of these studies, we highlight the gap between reality and available policies and practice. We conclude with some suggestions taking into account the changing realities of the family and the workforce. These include addressing work-family (work-life) issues as societal issues rather than individual problems, providing better support for the implementation of work-life policies, and reframing the work-life framework by going beyond the family to include other aspects of life as well as other strands of diversity besides gender.